Análise de desempenho de plataformas de educação a distância com arquitetura cliente-servidor utilizando teoria de filas - ALVES, Leonardo Antonio (2010)
In this work, we present an analytical model to predict the performance of the client-server system regarding an E-Learning platform. This approach is based on the queuing theory and can adequately describe the performance of an E-Learning platform and its parameters, such as the server response time. It is used a Poisson model to describe the traffic processes in the EaD system, comparing the output of the model to an E-Learning platform working at the MSD Education company. In this study, it was developed a precise tool for designing E-Learning platforms based on client-server model according to the increasing access demand.